Mise Au Point Des Techniques De Micropropagation Pour Une Multiplication Massive De Gladiolus Segetum Et Gladiolus Dubius - Emna El Chaieb; Faouzi Haouala (European Scientific Journal, ESJ, 2016)
Apical buds of corms of gladiolus (Gladiolus segetum and Gladiolus dubius) were cultivated on Murashige and Skoog (1962) medium supplemented with IBA 0.1 mg.l-1 and BA 2 mg.l-1. The number of newly formed buds was 3,8 and 4,13 buds per explants for respectively Gladiolus segetum and Gladiolus dubius. The in vitro Rooting need a supplement with auxin and sucrose. Rooting is not present in the control medium. The rate of rooting varied from 10 to 36%, depending on the species and the concentration of IBA in the medium. The Important rooting (36%) is observed for Gladiolus segetum in the presence of IBA 1 mg.l -1. Finally, the acclimatization is possible, these shoots rooted have formed many corms after 6 weeks of culture.